Home care services as a possibility to express art, creativity and access to technology - Janice de Moraes Blois; Maria do Horto Fontoura Cartana; Grace T.M. Dal Sasso; Cleusa Rios Martins (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This study is a reflection about art, creativity and technologies applied to nursing, within the process of contemporary care, particularly about the home care user and in the light on integral care. Over the last decades, the Brazilian Public Health System has gone through deep changes in its political, judicial and organizational elements, with an expressive expansion of the health assistance given to the population. The Home Care Policy comes as an initiative to implement new assistance logics, focusing on the promotion of the health and the prevention of health problems, aiming to overcome the "hospital-centered" model and in favor of the autonomy. We have realized that this policy is a possibility to express a broader way to understand health, in a search to organize the different skills and multi-professional practices and the interaction with the users. The concepts of art, creativity and technology are developed, relating them to the home care in the user's perspective